Comparison of hemocytes of 5th-instar nymphs of Rhodnius prolixus (Stal) and Rhodnius robustus (Larousse 1927), before and after molting (2015)
Background. The immune response of insects involves humoral factors and cellular elements known as hemocytes. There are different reports that explore the response of hemocytes to infections, but the effect that molting has on this response has not been explored so far. We hypothesized that there would be a change in the percentage of hemocytes as a response to the molting process.Objective. The aim of this work was to compare the hemogram (CBC), the formula, and the differential count of hemocytes in IV instar before molting and in V instar nymphs 24 hours after molting in two species: Rhodnius prolixus and Rhodnius robustus.Materials and methods. We assayed different staining methodologies including Giemsa, Alcian Blue pH 2.0, Alcian Blue pH 2.6, Gomori substrate, PAS (Schiff), Sudan Black and Papanicolau with positive controls for each one. In the Gomori staining, we observed lysosomes in the granulocytes and plasmatocytes, but the differentiation was better detected using Giemsa staining.Results. There were no statistically significant differences between the two species studied in plasmatocytes (p=0,053) or even in granulocytes (p=0,5). However, differences were significant in the prohemocytes (p=0,001) during the molting process in both Rhodnius prolixus and Rhodnius robustus.Conclusions. Significant differences in prohemocytes between nymphs of IV and V instar were detected. No significant differences in the amount of cells were observed between the two species and the two stages. These findings may be explained due to their role as precursor cell of prohemocytes.